Analysis of financial ratios before and after acquisition made at pt bank xyz tbk period 2001-2008 - Marse Dwi Karina (Institute of Accounting Research and Novation (IARN), 2021)
This research concerns about the financial performance analysis that was measured using the ratio of banking finance (CAMEL) at the time before and after the acquisition was carried out to PT XYZ during the period 2001 to 2008. The aim in this research was to know whether being gotten by the significant difference and to see factors that could influence the change of financial ratios performance before and after being carried out by the acquisition to PT XYZ. The independent's variable included CAR, ATTM, APB, NPL, PPAPAP, PPPAP, ROA, ROE, NIM, BOPO and LDR. There are two stages of analysis that is the descriptive analysis and the analysis of statistics with used paired sample t-test with the level of the significance of 5%. The results of the descriptive analysis showed that APB, NPL, ROA, ROE, BOPO, and LDR did not show results that were better than before the acquisition. The results of statistics showed that the difference that was significant before and after the acquisition was carried out in CAR, PPPAP, ROE, NIM, and LDR. Based on the results of the analysis indicated that this acquisition did not yet produce synergy as well as the impact that was better for PT XYZ, this could be caused by their strategy that was aggressive to carry out thedevelopmentor the expansion of efforts.